ANALISIS CROWDFUNDING SYARIAH BERDASARKAN PRINSIP SYARIAH COMPLIANCE SERTA PENERAPANNYA PADA PRODUK PERBANKAN SYARIAH - Fahmi Makraja; Abdul Mujib (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2023)
The presence of Financial Technology is a concrete manifestation of economic development in the digital era. One form of fintech development is the emergence of crowdfunding which is accessed via an internet network connection. The purpose of this research is to find out the implementation of the sharia crowdfunding method from the point of view of sharia compliance in Indonesia. The method used in this study is qualitative by using an empirical juridical approach. The results of this study conclude that the application of the sharia crowdfunding method to real sector economic transactions is in accordance with sharia principles, meaning that the sharia crowdfunding method is permissible according to Islamic law. The interrelated parties in this crowdfunding are the organizers, initiators and investors or donors as well as the Sharia Supervisory Board as the supervisory institution for the implementation of sharia crowdfunding. The application of crowdfunding in the development of Islamic banking products must be in accordance with sharia principles, namely avoiding the elements of magrib (maisir gharar and usury). The development of crowdfunding-based Fintech has grown rapidly in Indonesia so that special regulations are needed to regulate this so that unwanted things do not occur.